2024
DOI: 10.1039/d3sc04861f
|View full text |Cite
|
Sign up to set email alerts
|

Towards designer polyolefins: highly tuneable olefin copolymerisation using a single permethylindenyl post-metallocene catalyst

Clement G. Collins Rice,
Louis J. Morris,
Jean-Charles Buffet
et al.

Abstract: Using a highly active permethylindenyl-phenoxy (PHENI*) titanium catalyst, high to ultra-high molecular weight ethylene–linear-α-olefin copolymers are prepared in high yields, with exceptional comonomer affinity, and predictable, tuneable composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Following the synthesis of permethylindenyl-based metallocenes, Williams et al reported the synthesis of permethylindenyl CGC analogues of the type Me 2 SB­( R N,I*)­TiCl 2 ({(η 5 -C 9 Me 6 )­Me 2 Si­( R N)}­TiCl 2 , where I* = η 5 -C 9 Me 6 ). , Ethylene polymerization activities up to three times that of the Cp* (η 5 -C 5 Me 5 ) derivatives were reported, with more electron-donating amido fragments shown to result in increased catalytic activities . More recently, we have reported the permethylindenyl-phenoxy (PHENI*) ligand, offering exceptional performance in olefinic polymerizations producing ultrahigh-molecular-weight homopolymers and highly tunable copolymers. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the synthesis of permethylindenyl-based metallocenes, Williams et al reported the synthesis of permethylindenyl CGC analogues of the type Me 2 SB­( R N,I*)­TiCl 2 ({(η 5 -C 9 Me 6 )­Me 2 Si­( R N)}­TiCl 2 , where I* = η 5 -C 9 Me 6 ). , Ethylene polymerization activities up to three times that of the Cp* (η 5 -C 5 Me 5 ) derivatives were reported, with more electron-donating amido fragments shown to result in increased catalytic activities . More recently, we have reported the permethylindenyl-phenoxy (PHENI*) ligand, offering exceptional performance in olefinic polymerizations producing ultrahigh-molecular-weight homopolymers and highly tunable copolymers. …”
Section: Introductionmentioning
confidence: 99%
“… 25 More recently, we have reported the permethylindenyl-phenoxy (PHENI*) ligand, offering exceptional performance in olefinic polymerizations producing ultrahigh-molecular-weight homopolymers and highly tunable copolymers. 27 30 …”
Section: Introductionmentioning
confidence: 99%